Escherichia coli lipoprotein binds human plasminogen via an intramolecular domain - Gonzalez, Tammy; Gaultney, Robert A.; Floden, Angela M.; Brissette, Catherine A. (Frontiers in Microbiology, 2015)
Escherichia coli lipoprotein (Lpp) is a major cellular component that exists in two distinct states, bound-form and free-form. Bound-form Lpp is known to interact with the periplasmic bacterial cell wall, while free-form Lpp is localized to the bacterial cell surface. A function for surface-exposed Lpp has yet to be determined. We hypothesized that the presence of C-terminal lysines in the surface-exposed region of Lpp would facilitate binding to the host zymogen plasminogen, a protease commandeered by a number of clinically important bacteria. Recombinant Lpp was synthesized and the binding of Lpp to plasminogen, the effect of various inhibitors on this binding, and the effects of various mutations of Lpp on Lpp-plasminogen interactions were examined. Additionally, the ability of Lpp-bound plasminogen to be converted to active plasmin was analyzed. We determined that Lpp binds plasminogen via an atypical domain located near the center of mature Lpp that may not be exposed on the surface of intact E. coli according to the current localization model. Finally, we found that plasminogen bound by Lpp can be converted to active plasmin. While the consequences of Lpp binding plasminogen are unclear, these results prompt further investigation of the ability of surface exposed Lpp to interact with host molecules such as extracellular matrix components and complement regulators, and the role of these interactions in infections caused by E. coli and other bacteria.